2002
DOI: 10.1385/endo:18:2:179
|View full text |Cite
|
Sign up to set email alerts
|

Direct In Vitro Effects of Androgens and Estrogens on <E1>ob</E1> Gene Expression and Leptin Secretion in Human Adipose Tissue

Abstract: In the present study, we have explored, in vitro, the possibility that short exposure to androgens and estrogens for 24 h may directly influence leptin expression (ARNm and secretion) in sc adipose tissue from men and women. In men, only dihydrotestosterone at high concentration (100 nM) induced a reduction in leptin secretion and ob mRNA level. In women, 17beta-estradiol (10-100 nM) increased ob mRNA expression (+180 to +500%) and leptin release (+75%). Moreover, in adipose tissue of women, the estrogen precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 43 publications
4
59
0
3
Order By: Relevance
“…In monkeys, DHEA(S) has a circadian rhythm, characterized by a morning peak, which is in antiphase with the circadian plasma leptin rhythm (Downs et al 2001, Urbanski et al 2004. Furthermore, DHEA(S) is a precursor to testosterone, and previous work has shown that androgens such as testosterone can inhibit the release of leptin (Elbers et al 1997, Jockenhovel et al 1997, Wabitsch et al 1997, Machinal-Quélin et al 2002. Therefore, it is plausible that the absence of a circadian leptin rhythm in the old peri-and post-menopausal females, stems from a loss of androgenmediated leptin inhibition via DHEA(S).…”
Section: Discussionmentioning
confidence: 99%
“…In monkeys, DHEA(S) has a circadian rhythm, characterized by a morning peak, which is in antiphase with the circadian plasma leptin rhythm (Downs et al 2001, Urbanski et al 2004. Furthermore, DHEA(S) is a precursor to testosterone, and previous work has shown that androgens such as testosterone can inhibit the release of leptin (Elbers et al 1997, Jockenhovel et al 1997, Wabitsch et al 1997, Machinal-Quélin et al 2002. Therefore, it is plausible that the absence of a circadian leptin rhythm in the old peri-and post-menopausal females, stems from a loss of androgenmediated leptin inhibition via DHEA(S).…”
Section: Discussionmentioning
confidence: 99%
“…Both the long and short forms were shown to be present in a nonmalignant human breast epithelial cell line (Hu et al 2002) and some human breast cancer cell lines (Dieudonne et al 2002, Hu et al 2002, Laud et al 2002, Frankenberry et al 2006, indicating the potential for a paracrine mitotic interaction between leptin synthesized by the surrounding adipocytes and the target mammary cells. Laud et al (2002) reported that both forms occur in the ER-positive MCF-7 and T47D human breast cancer cell lines; they were also present in the epithelial cells of all of 20 primary breast cancers, only 5 of which were ER-positive.…”
Section: Leptinmentioning
confidence: 99%
“…Moleküler çalışmalar her iki hormonun "sinyal ileticisi ve transkripsiyon 3 aktivatörü (STAT3)" üzerine etkilerinin olduğunu ve östrojenin leptin kaynaklı STAT3 fosforilasyonunu arttırdığını göstermiştir. 28,29 Çalışmamızda ise BKİ ve BKİSDS değerleri birbirine yakın, PT grubunun leptin konsantrasyonları sağlıklı kontrol grubuna göre daha düşük bulunmuştur. Bu sonuçlar, antropometrik parametreler ne olursa olsun çevresel, genetik veya beslenme alışkanlıkları gibi diğer nedenlerin leptin düzeylerini etkilediğini düşündürmektedir.…”
Section: Discussionunclassified